COMPARATIVE OUTCOME FOLLOWING INTRODUCTION OF CHEST PHYSIOTHERAPY AND INCENTIVE SPIROMETRY AT A HOSPITAL SETTING AFTER MAJOR ABDOMINAL SURGERY (The Research of Medical Science Review, 2025)
Background: Post-operative respiratory complications are a major concern following major abdominal surgery. Techniques such as chest physiotherapy (CPT) and incentive spirometry are commonly used to improve pulmonary function and reduce complications like atelectasis and pneumonia. However, the comparative effectiveness of these two interventions remains unclear.Objectives: To compare the outcomes of chest physiotherapy and incentive spirometry in terms of reducing post-operative pulmonary complications, improving recovery time, and enhancing patient comfort following major abdominal surgery.Study Design & Setting: This was quasi-experimental study conducted at General Surgery and Surgical Oncology, Shaikh Zayed Hospital, Lahore the study was carried out between January 2024 and June 2024 involved patients who underwent major abdominal surgery.Methodology: A total of 120 patients were assigned to two groups: Group 1 (Chest Physiotherapy) and Group 2 (Incentive Spirometry). The primary outcomes measured included the incidence of post-operative pulmonary complications (atelectasis and pneumonia), length of hospital stay, time to first ambulation, and post-operative pain scores (VAS). Secondary outcomes included patient comfort and satisfaction scores. Data were analyzed using SPSS version 25, with significance set at p < 0.05.Results: The Chest Physiotherapy group had a significantly shorter hospital stay (6.1 ± 1.5 days) compared to the Incentive Spirometry group (7.2 ± 2.1 days, p = 0.01). Pain scores were significantly lower in the Chest Physiotherapy group on Days 1, 3, and 7. No significant differences were observed in pulmonary complications or time to first ambulation.Conclusion: Chest physiotherapy was more effective in reducing hospital stay and post-operative pain compared to incentive spirometry, but both methods were effective in promoting respiratory recovery after major abdominal surgery